Redes GPON como solução para FTTH - Cruz, Andrine Mariana Varela da (2014)
Given the necessity of delivering the most complete telecommunications services that require greater bandwidth, this work suggests the implementation of a gigabit passive optical network ( GPON ) solution as fiber to the home ( FTTH ) for a residential condominium . Currently most condos use the public telephone network for voice and data services. The proposed network is convergent (integrates data, voice and video) and aims to renew the legacy access network and the increased ability to service customers at a higher transmission speed. To achieve the proposed objectives, the literature survey of the principles of passive optical networks (PON) and transmission network was carried out architectures, fiber to the home, apartment or building, (FFTx). At the end of a project was established to service clients of a particular residential condominium. Which concludes that the GPON is one of the best solutions to take multiple telecommunications services residences, providing operators for an expansion of the number of subscribers.